Mechanism of inositol-requiring enzyme 1-alpha inhibition in endoplasmic reticulum stress and apoptosis in ovarian cancer cells - Barez, Shekufe Rezghi (J Cell Commun Signal, 2020)
IRE1α endonuclease is a key regulator of endoplasmic reticulum (ER) stress that controls cell survival/apoptosis in cancers. Inhibition of IRE1α endonuclease leads to decreased splice XBP1 which decreases cell proliferation and increases cell death in cancer cells. Therefore, this study investigated the effects and mechanism of STF-083010 (an IRE1α inhibitor) on the cell growth/apoptosis of ovarian malignant cells via the XBP1-CHOP-Bim pathway following the induction of ER stress (ERS). ERS in OVCAR3 and SKOV3 cells was measured using Thioflavin T staining. The expression of ER stress response genes was evaluated by QRT-PCR. The levels of XBP1(s), PERK, phospho-PERK, p-PP2A, ATF4, BIP/GRP78, CHOP, and Bim proteins were evaluated using western blotting. Cell viability and apoptosis in STF-083010 and Tunicamycin (Tm) co-treated cells were assessed using BrdU, MTT, Annexin V-FITC/PI staining, and caspases-12 and -3 activity assays. The results showed increased XBP1, CHOP, and ATF-4 mRNA expression levels as well as high protein aggregation in STF-083010 and Tm co-treated cells. The IRE1α inhibitor down-regulated sXBP1 and BIP proteins, while XBP-1, p-PERK, ATF-4, CHOP, and Bim proteins were up-regulated. STF-083010 reduced cell proliferation and induced apoptosis through the activation of caspases-12 and -3 and Bax/Bcl-2 protein expression. In summary, the present data revealed the effects of STF-083010 in ER stress and apoptosis as well as signaling via XBP1/CHOP/Bim mediators. Thus, STF-083010 is proposed as a new target for the control of ERS in ovarian cancer cells.